Commentary on: amnestic mild cognitive impairment and incident dementia and Alzheimer's disease in geriatric depression. (10th November 2014) - O'brien, John T.; Koopmans, Raymond; Rosness, Tor
<x content-type="archive" xml:space="preserve">Abstract</x> In this month's "Paper of the Month, " Steffens and colleagues (Steffens et al., 2014) report on the relationship between depression, mild cognitive impairment (MCI) and future risk of progression to dementia. It has long been known that there is a complex relationship between depression and cognitive impairment, with depression common in those with cognitive impairment and dementia, and subsequent cognitive decline frequent in patients with depression (Wallin et al., 2013). This relationship has often been difficult to study, not least because definitions have often been mutually exclusive. For example, many studies of MCI have excluded patients with depression. This is not unreasonable to increase diagnostic certainty and obtain a more "pure" group of those with MCI who are likely to progress to Alzheimer's disease, but of course at the same time limits the ability to determine interactions between MCI and depression. On the other hand, it is known that non-cognitive symptoms, most particularly depression, frequently occur in those with MCI and have been shown to increase the risk of likely future decline.